Usage of Fiber-Reinforced Resin Instruments in Interproximal Surfaces - Can-Karabulut, Deniz C.; Ozyurt, Perihan; Gurbuz, Ayhan; Gullu, Abdulkadir (European Journal of Dentistry, 2008)
Objectives: The aim of this study was to investigate the effects of fiber-reinforced resin burs on the surface roughness of a nanofilled composite.Methods: Average surface roughness values (Ra, m) were measured using a surface profilometer and surface textures after finishing procedures were evaluated using a scanning electron microscope (SEM). Thirty cylindrical specimens were prepared using sectional teflon molds. A nanofilled composite was chosen. After the preparation specimens were divided into three subgroups randomly. After profilometric measurements, representative samples of the mentioned finishing procedures were selected and SEM analyses were carried out.Results: Mylar strip group was statistically different from the other two groups (P<.05). The smoothest surfaces occurred when composite resin samples were light cured against the strips. On the other hand there was no statistical difference between fiber-reinforced resin burs and Sof-Lex discs (P>.05). For fiber-reinforced resin burs scratches and pitting which may be due to plucking of the filler particles during finishing were observed on the surface topography of the composite resin material. On the other hand, for the Sof-Lex discs although scratches were noticed on the surface topography, no pitting was observed.Conclusions: Fiber-reinforced resin burs can be preferred for the grinding of composite surplus in interproximal surfaces, where the use of Sof-Lex discs can be harmful to soft tissues. (Eur J Dent 2008;2:96-101)
Keywords: Fiber-reinforced resin burs; Nanofilled composite; SEM; Sof-Lex discs; Surface roughness.